Melalui Pendekatan Saintifik Model Pembelajaran Abad Ke-21 Metode Blended Learning untuk Meningkatkan Hasil Belajar Peserta Didik Mata Pelajaran Matematika Kd 3.2/4.2 Pokok Bahasan Sistem Persamaan Linear Tiga Variabel di Kelas X.IS.1 MAN 2 Kota Payakumb - Dewi Kemala (Departement of Mathematics Education, 2022)
This study is aimed to see and analyze the increasing of students learning result of mathematic subject in basic competency 3.2/3.4 about linear equation system three variables applying scientific approach the 21st century learning learning model in covid-19 pandemic learning at tenth grade, even semester of MAN 2 Payakumbuh, west Sumatra.This research was applying classroom action research. It consisted of two cycles where each cycle consisted of planning, action, reflection, and evaluation. This research has been conducted from august to November 2021. The data was processed and analyzed into percentage. The improvement in the average value of learning result for knowledge competence at the 1st cycle from 79,72 to 84,17 at the 2nd cycle and the result value for skill competences increased from 77,78 at the 1st cycle to 80,56 at the 2nd cycle. The students learning mastery for knowledge competence at the 1st cycle and the 2nd cycle is 32 students (88,89%) for skill competence have increased from 24 students (66,67%) at the 1st cycle become 33 students (91,67%) at the 2nd cycle from 36 students. The conclusion obtained from this research is the applying scientific approach the 21st century learning model in covid-19 pandemic learning can improved the students learning result.